Collaborative learning in modern active teaching methods; SGEM. 3rd International Multidisciplinary Scientific Conference on Social Sciences and Arts; Bk. 1, vol. 1 - Pozdeeva S. I. Svetlana Ivanovna; Fedorinova Z. V. Zoya Vladimirovna; Solonenko A. V. Aleksandra Vladimirovna; Saveljeva T. N. Tatjyana Nikolaevna (2016, 2016)
Title screen